Medios de comunicación y hábitos alimenticios de estudiantes de la Carrera de Electromecánica de la Universidad Nacional de Loja - Arévalo Yunga, Rosa Alicia (2015)
The research entitled MEDIA AND EATING HABITS OF STUDENTS OF THE RACE ELECTROMECANICA National University of Loja, assessed by a survey the influence of media on eating habits. This study is descriptive and cross-sectional, the universe consisted of 188 students; 3% were female and 97% male and 41% were same adolescent group and 59% for young people. The tabulation and analysis were performed using the tables and charts, resulting in which the media is the most widely used internet more than 4 hours used by 46.8% of students, followed by television, the same 72 % use up to 4 hours daily, thus become the most influential media because of the long hours they observe food advertising; which it is primarily responsible for the advertising of energy-dense foods and taking in the group of adolescents consume 52% more energy foods in the young and 57% consume more food trainers; the main food most consumed by young people and adolescents of both sexes lunch with 79% and 78% respectively, the most consumed snack in adolescents is the afternoon with 61%, unlike young people in the 64 % consume food in the morning. The results suggest that the media in addition to selling advertising influence lifestyles due to the long hours that youth and adolescents of different social strata use them daily. Keywords: media, eating habits, students, youth and adolescents.